The Moderating Role of Bank-Specific Factors on Commercial Bank Lending - Shadow Banking Nexus - Isayev, Mugabil (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2022)
This thesis examines the moderating role of commercial bank-specific factors on commercial bank lending - shadow banking nexus. To this aim, firstly, this thesis constitutes an initial attempt to examine bank risks and profitability effects on commercial bank lending-shadow banking nexus in emerging market economies (EMEs). One-step and two-step system GMM results suggest that commercial banks’ credit risk, capital risk and profitability have a key role in the bank lending-shadow banking nexus. Findings also reveal that shadow banking can act as both substitutes and complements to traditional banking. Moreover, high institutional demand and lower restrictions on bank activities are found to be among the main drivers of shadow banking expansion. Secondly, this thesis investigates whether bank-specific factors within the CAMELS framework moderates the linkage between commercial bank lending (CBL) and nonbank financial intermediation (NBFI). Both static (fixed effects and random effects) and dynamic (one-step and two-step system GMM) panel techniques are employed for the sample of 29 countries spanning 2002-2020. Empirical findings provide strong evidence for the complementarity hypothesis between commercial banking and NBFI sectors. Moreover, marginal effects of CBL on NBFI reveal that complementarity between two sectors depends on several commercial bank-specific characteristics. That is, a strong capital position, poor asset quality, high liquidity position, and high exposure to market risk seem to weaken the link (complementarity) between the two sectors.

ÖZ: Bu tez, ticari bankaya özgü faktörlerin ticari banka kredileri - gölge bankacılık bağlantısı üzerindeki düzenleyici rolünü incelemektedir. Bu amaçla, ilk olarak, yükselen piyasa ekonomilerinde (GOÜ) banka risklerinin ve karlılığının, ticari banka kredisi-gölge bankacılık bağlantısı üzerindeki etkilerini incelemeye yönelik çalışma oluşturuldu. Tek adımlı ve iki adımlı sistem GMM sonuçları, ticari bankaların kredi riski, sermaye riski ve karlılığının banka kredisi-gölge bankacılık bağında anahtar bir role sahip olduğunu göstermektedir. Bulgular ayrıca gölge bankacılığın geleneksel bankacılığın hem ikamesi hem de tamamlayıcısı olarak hareket edebileceğini ortaya koymaktadır. Ayrıca, yüksek kurumsal talep ve banka faaliyetlerine yönelik kısıtlamaların, gölge bankacılık genişlemesinin ana itici güçleri arasında yer almaktadır. Daha sonra, CAMELS çerçevesindeki bankaya özgü faktörlerin, ticari banka kredisi (CBL) ve banka dışı finansal aracılık (NBFI) arasındaki bağlantıyı etkileyip etkilemediğini araştırmaktadır. 2002-2020 yıllarını kapsayan 29 ülke örneğinde hem statik (sabit ve rastsal etki) hem de dinamik (tek adımlı ve iki adımlı sistem GMM) panel very analiz teknikleri kullanılmıştır. Ampirik bulgular, ticari bankacılık ve NBFI sektörleri arasındaki tamamlayıcılık hipotezi için güçlü kanıtlar sağlamaktadır. Ayrıca, CBL'nin NBFI üzerindeki marjinal etkileri, iki sektör arasındaki tamamlayıcılığın ticari bankalara özgü faktörlere bağlı olduğunu ortaya koymaktadır. Güçlü sermaye pozisyonu, düşük aktif kalitesi, yüksek likidite pozisyonu ve yüksek piyasa riskine maruz kalma, iki sektör arasındaki bağlantıyı (tamamlayıcılığı) zayıflattığı görünmektedir.
Doctor of Philosophy in Finance. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2022. Supervisor: Prof. Dr. Eralp Bektasş.
Keywords: Thesis Tez; Banking and Finance Department; Banks and Banking--Commercial Banks--Shadow Banking; Shadow banking; non-bank financial intermediation; CAMELS; bank – specific factors; emerging market economies; commercial bank lending; dynamic panel data